Orbitofrontal cortex encoding of reward delayed gratification in chronic pain - Gonçalo José Santos Araújo (2024)
Chronic pain induces structural and functional changes in several brain regions, including the orbitofrontal cortex (OFC), characterized by reduced gray matter and decreased dopaminergic transmission. Since dopamine is crucial for the OFC's optimal functioning, this decline impairs its performance. The OFC plays a key role in reward processing, particularly in monitoring and updating the value of expected outcomes. Additionally, it has been associated with regulation of impulsive behaviors by promoting the pursuit of more advantageous and delayed rewards. Thus, the changes caused by chronic pain likely contribute to the observed shift towards instant gratification over delayed in individuals with chronic pain. However, current evidence indicates contradictory roles for the OFC in delayed gratification, highlighting the need for further investigation. To address this problem, this study was designed in two phases. The first, aimed to validate whether, under conditions of chronic inflammatory pain, there is indeed a greater preference for instant rewards in a delayed gratification task (DGt). The second, explored the role of OFC in executing the DGt and how pharmacological modulation of dopamine D2 receptors (D2r) affected performance in DGt, both under chronic inflammatory pain. The DGt consisted of 2 retractable levers with different reward deliver contingencies: the "instant lever", which delivered 1 food-pellet if pressed 5 sec after exposure, and the "delayed lever", which delivered 3 food-pellets if pressed 10 sec after exposure. To induce the chronic inflammatory pain model, 50 μL of Complete Freund's Adjuvant (CFA) were injected into the dorsal side of the hindpaw. In the second part of the project, prior to induction of inflammatory pain, rats underwent to unilateral lesions of the OFC using quinolinic acid (0.4 µl, 0.18 M). Behavior performance was assessed 1, 2, and 3 weeks post-CFA injection. Each probe session comprises 3 treatments: vehicle (NaCl 0.9% w/v, IP), raclopride (antagonist D2r, 0.05 mg/kg, IP), and quinpirole (agonist (D2/3r) (0.05 mg/kg, IP). Mechanical noxious stimulation was assessed using von Frey filaments. The results revealed that both experimental groups preferred instant rewards. However, the difference between groups emerged during non-rewarded trials, as CFA group exhibited a higher preference for the instant lever. This similarity in rewarded trials was not observed after OFC lesions, as animals without pain showed a higher preference for delayed rewarded trials and instant non-rewarded trials. Conversely, CFA group showed similar results to their non-lesioned counterpart. Regarding D2r modulation, systemic administration of quinpirole increased lever-shifting, while raclopride decreased it. These results suggest that unilateral OFC lesions may impair the ability to update reward values, compromising associative learning, without increasing impulsivity. This impairment was not observed in CFA group, likely because chronic pain induces deficits similar to those caused by OFC lesions. Furthermore, quinpirole increased shifting behavior, while raclopride had the opposite effect, possible due to alterations in reward sensitivity, without affecting overall preference indices, likely due as result of a systemic rather than a localized effect.